I came a stranger : the story of a Hull-House girl - Polacheck, Hilda Satt, 1882-1967 (University of Illinois Press, 1989)
Biography of Hull-House activist and writer.
Keywords: Polacheck, Hilda Satt, -- 1882-1967.; Hull-House (Chicago, Ill.) -- History.; Hull-House (Chicago, Ill.); Jews -- Illinois -- Chicago -- Biography.; Chicago (Ill.) -- History.; Women -- United States -- History -- 20th century.; Women social reformers -- United States -- Biography.; Juifs -- Illinois -- Chicago -- Biographies.; Chicago (Ill.) -- Histoire.; Femmes -- États-Unis -- Histoire -- 20e siècle.; Réformatrices sociales -- États-Unis -- Biographies.; Jews.; Social reformers.; Women.; Women social reformers.; Illinois -- Chicago.; United States.; Autobiografie; 1900-1999; Polacheck, Hilda S.; Biographies.; History.